The Level of Student Literacy Towards The Sharia Cooperatives - Ropi Marlina; Juliana Juliana (Universitas Pendidikan Indonesia, 2020)
Abstract. This article is motivated by the wrong perception of the understanding and knowledge of Islamic cooperatives. The purpose of this study is to find out the level of student literacy in Islamic cooperatives. The method used is the quantitative descriptive method. The number of research samples amounted to 70 active students of the Indonesian Education University representing each faculty. The results showed that students did not fully understand the development agreement used in Islamic cooperatives included in the contract syirkah. However, in general, students' literacy toward usury and the compatibility of Islamic cooperatives with Islamic principles is largely understood. The implication of this research shows that there is a need to increase literacy to students as a younger generation, more specifically about the existing contractual agreements in Islamic cooperatives. Keywords. Sharia Banking, Sharia Cooperative, Syirkah, Student Literacy